Adult height is associated with health-related quality of life in an apparently healthy population - Vianto, Maiju (My University, 2026)
Purpose: In population-based studies, conflicting results have been obtained about the association of adult height and health-related quality of life (HRQoL). The present study aimed to assess this association in an apparently healthy middle-aged population, and to explore sex-related differences regarding perceptions of HRQoL among short, average and tall individuals Methods: A cross-sectional, observational study was conducted among 1,186 individuals aged 45–70 years. Study subjects had at least one cardiovascular risk factor, but no manifested cardiovascular disease, diabetes, chronic kidney disease, musculoskeletal and connective tissue disorders, neurologic disorders, pulmonary disorders or cancer. HRQoL was assessed with the EuroQol instrument EQ-5D-3L. Height was measured by study nurses. Results: The mean EQ-5D-3L summary index scores were higher in men than in women after adjustment with age (p <0.001). The perception of overall health status, measured with age-adjusted EQ-VAS scores, increased linearly with rising height in men (p=0.013), but not in women (p=0.66).There were no interactions between sex and height. In men, categories of height showed a negative linear relationship with anxiety/depression dimension of the EQ-5D-3L (age-adjusted p=0.042). Conclusion: Tall men have better HRQoL than tall women in an apparently healthy, middle-aged population. The taller the man, the better perception of health and the less anxiety/depression. Mean population heights should be acknowledged when comparing HRQoL in different datasets and ethnic groups.
Keywords: Health-related quality of life; EQ-5D-3L; body height; anxiety; depression